Influence of the Quaternary Glacial Cycles and the Mountains on the Reticulations in the Subsection Willkommia of the Genus Centaurea - Ben-Menni Schuler, Samira; López-Pujol, Jordi; Blanca, Gabriel; Vilatersana, Roser; Garcia-Jacas, Núria; Suárez-Santiago, Víctor N. (Frontiers in Plant Science, 2019)
Late Neogene and Quaternary climatic oscillations have greatly shaped the genetic structure of the Mediterranean Basin flora, with mountain plant species tracking warm interglacials/cold glacials by means of altitudinal shifts instead of broad latitudinal ones. Such dynamics may have enhanced population divergence but also secondary contacts. In this paper, we use a case example of subsection Willkommia of Centaurea (comprising three narrowly distributed endemic species, Centaurea gadorensis, C. pulvinata, and C. sagredoi) to test for reticulate evolution and recurrent hybridizations between nearby populations. For this, we combine analyses of genetic diversity and structuring, gene flow and spatial correlation, and ecological niche modeling. Our results support the contention that the current genetic structure of the three species is the result of historical gene flow at sites of secondary contact during the glacial periods, followed by isolation after the retraction of populations to the middle-upper areas of the mountains during the interglacial periods. The extent and direction of the gene flow was determined largely by the location of the populations on mountainsides oriented towards the same valley or towards different valleys, suggesting the intermountain valleys as the areas where secondary contacts occurred.